CoA Synthase influences adherence-independent growth and survival of mammalian cells in vitro - Breus, O.S.; Nemazanyy, I.O.; Gout, I.T.; Filonenko, V.V.; Panasyuk, G.G. (Вiopolymers and Cell, 2009)
Aims. We aimed to study the influence of the expression level, activity and subcellular localization of CoA Synthase (CoASy) on anchoring independent growth and viability of in vitro cultured cells. Methods. Abilities of cells to form colonies in semisolid agarose and survive in growth factor depleted conditions were tested. A panel of HEK293 stable cell lines which over express wild type, catalytically inactive or mitochondria association mutants of CoASy were used in the study. Effects of CoASy down regulation by siRNA on malignant phenotype of HepG2 cells have been studied. Results. We report here that changes in CoASy expression level affect anchoring independent growth and viability of mammalian cells. Catalytic activity of CoASy and its association with mitochondria are crucial for mediating of the observed effects. Conclusions. Presented data indicate CoASy has positive impact on activity of signalling pathways in the cell and reveal unknown before functional link between signal transduction and metabolism.